Comparative study of digestibility of native legumes with sheeps and goats in the "sertao" of Ceara II. In vivo digestibility of mata-pasto hay - Barros, Nelson Nogueira; Freire, Luiz Carlos Lopes; Lopes, Expedito Aguiar; Kawas, Jorge; Johnson, William L. (Pesquisa Agropecuaria Brasileira, 1991)
Six sheep and six goats, adults and castrated males were used to evaluate the nutritive value of the mata-pasto (Cassia spp.) hay. Experimental animals were kept in elevated metabolism crates for a 14-day adaptation period followed by a seven day collection period of total feces and urine. The animals were given ad libitum access to forage consumption, water and mineralized salt. Crude protein, neutral detergent fiber and KMnO4 lignin contents were, respectively, 7.6, 66.7 and 14.2%. Values of dry matter and crude protein intakes of sheep were significantly (P < 0.01) greater than those of goats. For sheep, intake of digestibile dry matter was 24.3 g/kg.75/day and the digestibilities of organic matter, dry matter and N were respectively 53.9, 60.0 and 59.5%. Due to physiological status of goats values of those parameters were not obtained for this animal specieis. Sheep N balance was superior (P < 0.05) to the goats. The mata-pasto hay showed a greater potential of utilization by sheep than by goats.